FRECAST: message transmission model in dense graphs for ad hoc networks. (13th February 2006) - Bakar, Sakhinah Abu; Salleh, Shaharuddin; Lee, Muhammad Hisyam
Ad hoc network is a self-adapting wireless network formed from special function nodes. The network is self-organised where each node acts as a router for transmitting and receiving messages. This enables the network to form a network in the absence of communication infrastructures such as base stations. In this paper, we discuss the problem of single, multiple and broadcasting message transmission in highly-dense ad hoc networks. The problem requires finding the shortest paths and minimum spanning tree in order to make the message transmission optimum. We present a visualisation model called FRECAST based on a routing protocol called WRP.